2020
DOI: 10.1021/acsnano.9b08693
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Targeting by αvβ3-Integrin-Specific Lipid Nanoparticles Occurs via Phagocyte Hitchhiking

Abstract: Although the first nanomedicine was clinically approved more than two decades ago, nanoparticles’ (NP) in vivo behavior is complex and the immune system’s role in their application remains elusive. At present, only passive-targeting nanoformulations have been clinically approved, while more complicated active-targeting strategies typically fail to advance from the early clinical phase stage. This absence of clinical translation is, among others, due to the very limited understanding for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 68 publications
3
61
0
Order By: Relevance
“…[107][108][109][110][111] Marios Sofias et al showed that α v β 3 -targeted particles accumulate in tumors via phagocyte hitchhiking rather than by canonical receptor-ligand binding within the tumor. 103 In this study, both targeted and non-targeted nanoparticles were engulfed by circulating phagocytes (e.g. neutrophils and monocytes) and shuttled to tumors.…”
Section: Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…[107][108][109][110][111] Marios Sofias et al showed that α v β 3 -targeted particles accumulate in tumors via phagocyte hitchhiking rather than by canonical receptor-ligand binding within the tumor. 103 In this study, both targeted and non-targeted nanoparticles were engulfed by circulating phagocytes (e.g. neutrophils and monocytes) and shuttled to tumors.…”
Section: Reviewmentioning
confidence: 95%
“…Moreover, it is now appreciated that nanoparticles can enter tumors by a variety of mechanisms, including passively via EPR, 99,100 dynamically via vascular vents, 101 actively via endothelial transport, 102 and via hitchhiking on-board phagocytes. 103 One study of note was conducted by Perrault et al to systematically study how particle size (10-100 nm) influenced the pharmacokinetics of nanoparticles. 104 The authors showed that 60-100 nm diameter particles had the highest tumor accumulation but smaller particles like the 20 nm diameter nanoparticles tested have improved tumor penetration.…”
Section: Reviewmentioning
confidence: 99%
“…Since F4/80-positive phagocytes are involved in taking up nanomaterials in several tissues (e.g. F4/80 + Ly6C -M2-like macrophages in tumor, F4/80 + CLEC4F + Kupffer cells in liver, and F4/80 + macrophages in spleen [24][25][26]), we paid particular attention to analyzing CCPM co-localization with these cells. Additionally, since emerging evidence indicates that NP enter tumors via endothelial transcytosis, we also studied the internalization of CCPM by CD31-positive endothelial cells [27].…”
Section: Ccpm Distribution At the Cellular Levelmentioning
confidence: 99%
“…This is in concordance with the in vivo pattern observed for most of the nanoparticles, especially lipid nanoparticles, such as liposomes and nanoemulsions. 19 , 24 , 37 , 44 Remarkably, NOTA-SNs have a relatively long circulation time, showing a 10% of the injected dose in the bloodstream 4 h after intravenous injection. This in vivo pattern differs from other 68 Ga-labeled emulsions recently reported, with a shorter circulation half-life, mainly due to differences in size and composition.…”
Section: Resultsmentioning
confidence: 99%